THE EFFECT OF GANZE METHOD ON THE EIGHTH GRADE STUDENTS’ READING COMPREHENSION AT SMPN 16 KOTA TANGERANG - Farida Riyadi; Yudhie Indra Gunawan; Moh Iqbal Firdaus; Abdul Rohim (Universitas Muhammadiyah Tangerang, 2022)
The aim of the research is to know the effect of using Ganze Method is effective to be used on the Eight Grade Students’ Reading Comprehension at SMPN 16 Kota Tangerang. Ganze Method is a method of teaching reading comprehension that gives the opportunities to the students to outline and translate the text by the students own words. Reading comprehension is complex highly process that increases students’ knowledge, the context of the text, and expectation by interaction between the students. Ganze method applied in teaching reading could be an effective method. It was very helpful for the improvement of the students’ reading comprehension. The method used in this research was quantitative method. The design of this research was quasi - experiment to know the effectiveness of using Ganze method on the students’ reading comprehension. The result can be seen that using Ganze Method as the method is effective on the students’ reading comprehension. It could be seen from the average of post - test result in Experimental Class was 80.98, and the average of pre-test was 61.25. The average of post-test result in controlled class was 67.42, and the average of pre-test was 60.11. The result of the t – test of post-test also showed that there was a significant difference between experimental and control class, t – count of ɑ = 5% and dƒ = 68 was 4.92, and for t – table was 1.99. The calculation proved that t-count was higher than t-table. It can be concluded that Ganze method can be considered to use for teaching reading comprehension since it can expand the students’ knowledge and information with the text easily.